Contribution of Executive Functions to Learning Sequential Actions in Young Children. Issue 4 (23rd December 2020) - Yanaoka, Kaichi; Saito, Satoru
Abstract : This study examined whether executive functions impact how flexibly children represent task context in performing repeated sequential actions. Japanese children in Experiments 1 ( N  = 52; 3–6 years) and 2 ( N  = 50, 4–6 years) performed sequential actions repeatedly; one group received reminders. Experiment 1 indicated that reminders promote flexible changes in contextual representations. Experiment 2 observed such effects in younger children and showed executive functions were associated with the flexible representation of task context. Reminders did not perfectly compensate for the role of executive functions but wiped out individual differences in executive functions that contribute to children's acquisition of routines. Therefore, setting goals before context‐dependent actions is necessary, but not sufficient, to modulate contextual representations in routines.